RUANG LINGKUP KEJAHATAN EKONOMI - -, Supriyanta (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
Abstract Economic crimes have special characteristic because depend on economic system and development storey, level an society, its scope is very wide of covering crimes in banking area, money changing, computer crimes, corporation crimes, and others. Keywords: Economic crimes